Postanalityczne perspektywy ogólnej refleksji nad prawem - Sulikowski, Adam (Wydawnictwo Uniwersytetu Wrocławskiego, 2015)
The main purpose of this paper is to examine the applicability of methods and tools offered by the postanalytic philosophy in the field of legal theory. The author notes that after the crisis of the traditional linguistic approach to the concept of law, the main successor to analytic tradition in legal theory is the naturalistic approach based on evolutionism and latest trends in the natural sciences.In contrast, postanalytic topics are developed by critical theories. In the new situation, after the weakening of traditional legal controversies, the dispute between naturalists and postanalytic critics could become a major controversy in the field of contemporary legal theory.
Keywords: teoria prawa; filozofia poanalityczna